Subcutaneous administration of bovine superoxide dismutase protects lungs from radiation-induced lung injury. (October 2015) - Antonic, V.; Rabbani, Z. N.; Jackson, I. L.; Vujaskovic, Z.
Abstract Background. The objective of the present study was to determine whether single administration of the antioxidant enzyme bovine superoxide dismutase (bSOD) after radiation therapy (RT) mitigates development of pulmonary toxicity in rats. Methods. Female F344 rats (n = 60) were divided among six experimental groups: (1) RT, single dose of 21 Gy to the right hemithorax; (2) RT + 5 mg/kg bSOD; (3) RT + 15 mg/kg bSOD; (4) No RT; (5) sham RT + 5 mg/kg bSOD; and (6) sham RT + 15 mg/kg bSOD. A single subcutaneous injection of bSOD (5 or 15 mg/kg) was administered 24 h post-radiation. The effects of bSOD on radiation-induced lung injury were assessed by measurement of body weight, breathing frequency, and histopathological changes. Immunohistochemistry was used to evaluate oxidative stress (8-OHdG+, NOX4+, nitrotyrosine+, and 4HNE+ cells), macrophage activation (ED1+), and expression of profibrotic transforming growth factor-β or TGF-β in irradiated tissue. Results. Radiation led to an increase in all the evaluated parameters. Treatment with 15 mg/kg bSOD significantly decreased levels of all the evaluated parameters including tissue damage and breathing frequency starting 6 weeks post-radiation. Animals treated with 5 mg/kg bSOD trended toward a suppression of radiation-induced lung damage but did not reach statistical significance. Conclusions. The single application of bSOD (15 mg/kg) ameliorates radiation-induced lung injury through suppression of reactive oxygen species/reactive nitrogen species or ROS/RNS-dependent tissue damage.